(untitled) (Revista Sistemas de Producción Agroecológicos, 2023)
Colic in horses is a common abdominal condition that can range in severity from mild to life-threatening. Determining whether or not a colic is surgical is essential to making appropriate treatment decisions. The basic criteria to assess whether colic in horses is surgical or not include assessment of the degree of pain, physiological signs, assessment of the mucous membranes, digital rectal examination, intestinal sounds on auscultation, response to NSAIDs, abdominal ultrasound results, and patient evolution time, among others. In general, surgical cramps are usually associated with mechanical processes such as intestinal obstructions, torsions or hernias, which require surgical intervention for correction. On the other hand, non-surgical cramps can be due to less serious problems, such as intestinal spasms or digestive irritations, which can often be treated with medications and conservative therapies. It is important to note that colic in horses is a medical emergency, and any suspicion of colic should be treated as a serious situation and requires immediate veterinary attention.